P088 Mucosal CD103+ CD4+ and CD103+CD8+ T-cell subsets in the gut of inflammatory bowel disease patients at diagnosis and during follow-up. (16th January 2018) - Roosenboom, B; Smids, C; Wahab, P; Groenen, M; Van Koolwijk, E; Van Lochem, E; Horjus Talabur Horje, C
Abstract: Background: Recently, a pro-inflammatory role has been suggested for CD103+ CD4+, but not for the CD103+ CD8+ mucosal T-cell subset in inflammatory bowel disease (Lamb et al 2016). As the CD103 integrin is the target of new therapies with anti-β7 monoclonal antibodies, it is important to analyse the numbers of the different mucosal lymphocyte subsets in active disease and remission. Here, we aimed to study the frequencies of different CD103+ T-cell subsets in newly diagnosed, untreated IBD patients at baseline and during follow-up, compared with healthy controls (HC). Methods: Newly diagnosed patients with Crohn's disease ( n = 75; CD), ulcerative colitis ( n = 49; UC) and HC ( n = 16) were prospectively included. Baseline biopsy specimens were available in all patients. Follow-up biopsy specimens were analysed from 54 IBD patients (27 with active disease and 27 in remission). Immunophenotyping was performed on biopsy specimens by flow cytometry identifying different lymphocyte subpopulations. Mucosal T cells (CD3+CD103+, CD3+CD103+CD4+, CD3+CD103+CD8+) and non-mucosal T cells (CD3+CD103-CD4+, CD3+CD103-CD8+) were expressed as median percentages (%) of the total T-cell population (CD3+) and as a proportion of CD4+ or CD8+ T-cell subsets with corresponding interquartile range (IQR). Results: At initial diagnosis IBD patients had lower % CD3+CD103+, 11% (IQR 7–21) for CD and 13% (7–31) for UC patients, compared with HC (40% (26–86), p = 0.001). The % CD3+CD103+CD4+ was 3% (1–5) in IBD (4% of total CD4+ T cells) and 5% (5–7) in HC (11% of total CD4+ T cells, p = 0.007). The %CD3+CD103+CD8+ in IBD was 9% (4–15, 33% of total CD8+ T cells) and in HC 42% (23–57, 83% of total CD8+ T cells, p = 0.001). The majority of CD3+CD103- T-cell subsets in active IBD at baseline was represented by CD103-CD4+ T cells (65% (52–74), in HC 30% (21-50), p = 0.001), while CD103-CD8+ in IBD was 22% (15–27) and in HC 13% (10–20), p = 0.001). When endoscopic remission is seen in IBD patients during follow-up, all frequencies of CD103+ T-cell subsets approach percentages comparable to HC. Conclusions: Active mucosal inflammation in IBD patients is associated with decreased percentages CD3+CD103+ T-cell subsets. The CD103+ CD8+ T-cell subset is lower in active disease compared with healthy controls. Endoscopic remission in IBD is associated with normalisation of the mucosal T-cell profiles, also the CD103+CD8+ T-cell subset. The suggested pro-inflammatory CD103+ CD4+ T cells represented only a minority of the total mucosal (CD103+) T-cell subset. It is mainly the CD4+CD103− T-cell subset that infiltrates the inflamed colon in IBD. These results challenge the pro-inflammatory role of these CD103+CD4+ T cells in IBD patients.